2015
DOI: 10.3389/fmicb.2015.01399
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae: Development of Carbapenem Resistance due to Acquisition of blaNDM-1 During Antimicrobial Therapy in Twin Infants with Pneumonia

Abstract: Objectives: To identify the mechanism of in vivo development of carbapenem resistance in Klebsiella pneumoniae.Methods: Seven sequential isolates of K. pneumoniae were obtained from twin infants with pneumonia. Antimicrobial susceptibility testing was performed by agar dilution method. Carbapenemases including KPC and MβL were initially screened using phenotypic methods, and carbapenemase-encoding genes were identified by polymerase chain reaction and amplicon sequencing. Plasmids of all clinical isolates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…9,21 Previous studies analyzed the use of broad-spectrum antibiotics (such as carbapenems), urinary catheters, and mechanical ventilation as the risk factors for acquiring CRE strains among hospitalized patients. 22 In the current study, the rate of multidrug resistance among K. pneumoniae isolates was 86.6%.…”
Section: Discussionmentioning
confidence: 52%
“…9,21 Previous studies analyzed the use of broad-spectrum antibiotics (such as carbapenems), urinary catheters, and mechanical ventilation as the risk factors for acquiring CRE strains among hospitalized patients. 22 In the current study, the rate of multidrug resistance among K. pneumoniae isolates was 86.6%.…”
Section: Discussionmentioning
confidence: 52%
“…In 2010, Rodríguez-Avial reported that the mechanism was bla VIM-1 gene acquisition [37]. In 2015, Junying Zhu reported that the mechanism was bla NDM-1 gene acquisition [27]. CMY .…”
Section: Rasmussen Et Al and Andres Opazo Et Almentioning
confidence: 99%
“…It was discovered that ST37 are international clones associated with multidrug-resistant K. pneumoniae such as extended-spectrum β-lactamase, AmpC or carbapenemase producers [26]. Recently, NDM-1-producing K. pneumoniae belonging to ST37 were reported in China [27], which indicated that multidrug-resistant K. pneumoniae ST37 have been identified in our country. The bla OX A-1 -producing K. pneumoniae has been reported in some sequencing types, such as ST48, ST15 and ST23 [28].…”
mentioning
confidence: 94%
“…The increasing burden of CRE infections, the high rate of treatment failure, the emergence of resistance during treatment [5,6] and the dearth of novel antimicrobial agents highlight the urgency to investigate effective approaches for treating these infections. Polymyxins [polymyxin B (PMB) and polymyxin E (colistin)] are rapidly bactericidal against KPC-producing K. pneumoniae [7].…”
Section: Introductionmentioning
confidence: 99%